Strategi Komunikasi Pramuwisata dalam Menjaga Eksistensi Pariwisata Bali - I Dewa Ayu Hendrawathi Putri; Ni Ketut Sri Ratmini (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2018)
The world of communication tourism has an important role as a medium to seek or collect information, especially in presenting the package tour (package tour). Indonesia as a nation that is building, we realize very well that the success of this nation will depend on ourselves rather than to others. Intense competition among nations (tough, fierce competition among Nations), in this case determinants that will be able to answer is the quality of human resources in various layers and various sectors both private and government. Which tourism has become the mainstay sector is expected as "Prime Mover" in the national economic development, so it takes strategic steps in its growth in Asia Fasifik. The implementation of Balinese Cultural Tourism is carried out based on the principle of benefit, kinship, independence, balance, sustainability, participatory, sustainable, equitable and equitable, democratic, equality and unity which is imbued with the values of Hinduism by applying the Tri Hita Karana philosophy. Given the communication also plays an important role in the development of tourism in our country including Bali. Indonesia's tourism competitiveness (including Bali) is relatively somewhat winning when it comes to cheap prices, while on the other hand such as infrastructure, humanresources are far behind, so for the future there will be no significant effort to improve the quality of cheap products, and a thing that deviates from the purpose of tourism development especially for the area of Bali, namely the development of cultural tourism.